Helping Students Bridge Inferences in Science Texts Using Graphic Organizers. Issue 2 (26th May 2016) - Roman, Diego; Jones, Francesca; Basaraba, Deni; Hironaka, Stephanie
Abstract: The difficulties that students face when reading science texts go beyond understanding vocabulary and syntactic structures. Comprehension of science texts requires students to infer how these texts function as a unit to communicate scientific meaning. To help students in this process, science texts sometimes employ logical connectives (e.g., because, therefore ) that serve as landmarks that students can use to create a mental model of the text. Yet, how often are logical connectives used to mark inferences in science texts, and what can teachers do to support their students when these connectives are absent? This article discusses the frequency and types of logical connectives in four science textbooks and illustrates the types of obstacles that science texts present for students in their inference‐making process. Further, this article offers teachers a practical strategy that they can use to apprentice their students into the ways that science texts function to communicate scientific concepts.